The Oscars - Atkinson, John, 1968- (Pocket Essential Ser., 2001)
Pocket Essentials is a dynamic series of books that are concise, lively, and easy to read. Packed with facts as well as expert opinions, each book has all the key information you need to know about such popular topics as film, television, cult fiction, history, and more. This completely unauthorized guide to the Oscars explains how the Academy Awards can help us to understand the history of Hollywood. In a decade-by-decade account, it details how the Academy endorsed or rejected industry trends, be they technical, artistic, or political. Also included is a full list of Oscar winners in every category, as well as the author's own nominations for Worst Oscar-nominated Films and Shocking Oscar Oversights, making it the best-value, most up-to-date guide available to this annual public celebration of the movies.